The Effect Of Lignite Quality On CO2 Emissions And Cost Of Power Production From Western Macedonia Power Plants - K. Kavouridis (Society for Mining, Metallurgy & Exploration, 2006)
The competitiveness of power production from lignite depends on the ability of coal industry to meet CO2 emissions limits, as specified by the Kyoto protocol. According to the National Allocation plan issued by EC, power plants should reduce CO2 emissions to a certain level, other-wise they will be obliged to cover the difference buying CO2 certificates through the Emission Trading Scheme. These charges will increase the operating cost of current units, as well as the investment cost for new units. To predict the increase in the marginal cost of electric power produced from the current plants of Western Macedonia, an emissions factor (CO2 t/MWh) for various units has been computed. Based on the algorithm used, this factor depends on the calorific value of the lignite, the efficiency of the power plant and the oxidation factor of the unit. For lignite plants with efficiency ~37%, CO2 emissions factor ranged from 1.19 t/MWh to 1.32 t/MWh. The increase in the marginal cost of kWh, as compared to the values of CO2 certificates, is higher in units fed with low quality lignite and worsens if the efficiency of the unit is low too. Also the presence of calcareous minerals in lignite increases the CO2 emissions and consequently the cost of power generation.